Mobile Wireless Middleware, Operating Systems, and Applications Third International Conference, Mobilware 2010, Chicago, IL, USA, June 30 - July 2, 2010. Revised Selected Papers - Cai, Ying.; Magedanz, Thomas; Li, Minglu; Xia, Jinchun; Giannelli, Carlo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the thoroughly refereed proceedings of the Third International Conference on MOBILE Wireless MiddleWARE, Mobilware 2010, held in Chicago, USA, in June/July 2010. The 23 revised full papers presented were carefully reviewed and selected from 35 contributions. The papers are organized in topical sections on location and tracking supports and services, human-computer interface for mobile devices, mobility management and handoff management, novel applications and communication protocols for wireless networks, and mobile intelligent middleware.
Session 1: Novel Applications and Communication Protocols for Wireless Networks (Chair: Paolo Bellavista) -- A Secure Mobile OTP Token -- ISI and ICI Suppression for Mobile OFDM System by Using a Hybrid 2-Layer Diversity Receiver -- Using Smartphones to Detect Car Accidents and Provide Situational Awareness to Emergency Responders -- Session 2: Mobility Management and Handoff Management (Chair: Thomas Magedanz) -- XtreemOS-MD: Grid Computing from Mobile Devices -- The Proxy-Based Mobile Grid -- Access Network Discovery and Selection in the Future Broadband Wireless Environment -- Internet Connectivity Sharing in Multi-path Spontaneous Networks: Comparing and Integrating Network- and Application-Layer Approaches -- Session 3: Human-Computer Interface for Mobile Devices (Chair: Honggang Wang) -- Prototyping Convergence Services on Broadband Networks -- Adaptive Online Deployment for Resource Constrained Mobile Smart Clients -- Addressing Challenges with Augmented Reality Applications on Smartphones -- Location Cognition for Wireless Systems: Classification with Confidence -- Session 4: Mobile Intelligent Middleware (Chair: Ying Cai) -- Towards an Elastic Application Model for Augmenting Computing Capabilities of Mobile Platforms -- A Self-organizing Approach for Building and Maintaining Knowledge Networks -- Dynamic Adaptive Middleware Services for Service Selection in Mobile Ad-Hoc Networks -- Session 5: Location-Aware and Context-Aware Networking and Computing (Chair: Chris Thompson) -- An Object-Oriented Model in Support of Context-Aware Mobile Applications -- A Context Aware Interruption Management System for Mobile Devices -- Applying Behavioral Detection on Android-Based Devices -- Context-Enhanced Web Service Invocations in Mobile Business Processes -- Session 6: Short Papers (Chair: Paolo Bellavista) -- Power Aware with the Survivable Routing Algorithm for Mobile Ad Hoc Networks -- Testing and Evaluating of Predictive Data Push Technology Framework for Mobile Devices -- Service Space Portability Validation Modeling the Vehicular Context -- Experiences from Developing a Context Management System Applied to Mobility -- International Workshop on Mobile and Location-Based Business Applications (MAPPS 2010) -- The Relationship between User Location History and Interests in Products and Services -- Predicted and Corrected Location Estimation of Mobile Nodes Based on the Combination of Kalman Filter and the Bayesian Decision Theory -- Enhancing Customer Privacy for Commercial Continuous Location-Based Services -- SociCare: Towards a Context Aware Mobile Community Emergency System -- A Workflow Definition Language for Business Integration of Mobile Devices -- Adaptivity Types in Mobile User Adaptive System Framework -- International Workshop on Mobile Multimedia Networking (IWMMN 2010) -- Bootstrapped Low Complexity Iterative Decoding Algorithm for Low Density Parity Check (LDPC) Codes -- Quick Prototying of Multifacete Interface for Healthcare Wireless Sensor Network -- An Evaluation of Mobile End Devices in Multimedia Streaming Scenarios -- An Extended IGMP Protocol for Mobile IPTV Services in Mobile WiMAX -- Optimal Expected Discounted Reward of a Wireless Network with Award and Cost -- A Spectrum Sharing Scheme in Two Cellular Wireless Networks -- A Perspective on Estimation of Available Capacity in Wireless Networks -- Mobile Healthcare Infrastructure with Qos and Security -- A Survey on the Cross-Layer Design for Wireless Multimedia Sensor Networks -- A Survey on Cognitive Radio Networks -- A Comprehensive P-Persistent Algorithm in Multi-channel and Multi-interface Cognitive Network.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Computer Communication Networks; Information Systems Applications (incl.Internet).; User Interfaces and Human Computer Interaction; Software Engineering; Information Storage and Retrieval; Artificial Intelligence (incl. Robotics).